Response of the sweet potato crop (Ipomoea batatas) to the application of edaphic bioinputs: Agroindustria - López Castro, Jennifer Milena (2025)
This study focused on evaluating the agronomic and productive response of sweet potato (Ipomoea batatas) variety INIAP-Toquecita to the application of various soil bioinputs. The study took place at INIAP’s Portoviejo Experimental Station in Ecuador, from July to December 2022. The effects of several bioinputs, including diatoms, efficient microorganisms, biochar, earthworm humus, and organic matter, on various agronomic parameters were analyzed. The findings revealed statistically significant effects of these bioinputs on variables such as rooting rate, foliage cover, root biomass, root proliferation, aboveground biomass yield, commercial tuberous root production, leaf chlorophyll content, and nutrient concentrations in both soil and plant tissue. Biochar proved particularly effective in promoting vegetative growth, increasing vine proliferation per plant (9 vs. 6 vines·plant-1 in other treatments) and aboveground biomass production (24.17 t·ha-1). Vermicompost achieved the best initial establishment (100%) and the highest yield of commercial tuberous roots (24.90 t·ha-1). The addition of plant residues generated the highest concentration of foliar chlorophyll (range 41.86-45.93). At the end of the cycle, all treatments maintained adequate nutritional status, with significant absorption of phosphorus and iron. The results suggest that these bioinputs are an effective alternative to conventional chemical fertilization in sweet potato cultivation, with specific benefits for each, depending on the production objective.